EXPERIMENTAL AND NUMERICAL SIMULATION OF ELASTIC HONEYCOMB STRUCTURES BY 3D PRINTING (MT) - HOU YunYou; ZHANG Jie (Jixie qiangdu)
Transportation and human protection industry constantly demands for lightweight and better energy absorption materials and structures. By designing customizable porous materials, the mechanical properties and energy absorption of hexagonal honeycomb-structured polydimethylsiloxane（PDMS） were investigated through experiments and numerical simulations. PDMS has adequate viscoelastic properties for 3D directing ink writing（DIW）, therefore the honeycomb structures with different line widths were fabricated through optimizations of the printing speed and air pressure. Quasi-static compression tests were performed on the fabricated samples to evaluate their mechanical properties and energy absorption. The results show that the average stress in the plateau stage of the honeycomb structure increase with the increase of the line width, but is anisotropy. The honeycomb structure with line width of 900 μm has highest energy absorption of 0.018 J/cm~3. The corresponding finite element analysis were in agreement with the experimental results.